Using social networking applications to facilitate change implementation processes: insights from organizational change stakeholders. Issue 7 (26th June 2020) - Naeem, Muhammad
Abstract : Purpose: The failure rate of change is high amongst countries and cultures where collectivism, destructive politics and resistance are high. Therefore, change leaders are more focused on exploring how they can create networking and socialization amongst major organizational stakeholders that can minimize detrimental cynicism and lobbying during change implementation. This study is an attempt to shed light on how Social Networking Applications (henceforth SNAs) can facilitate change implementation processes in the insurance sector. Design/methodology/approach: The individual reaction and interaction realities during the change process cannot be discovered once and for all as there are varied perspectives on the same subjects. Therefore, a social constructionist position was used to understand the different realties of change managers and change recipients using the context of insurance sector. Findings: The study documented how SNAs can play an active role in addressing the concerns of employees as well as managing and protecting knowledge sharing to facilitate the change implementation process. The collaborative and interactive nature of SNAs can enhance richness in knowledge sharing and can facilitate the participation of employees. Therefore, management should monitor these platforms as a means to improve the change process and to address the concerns of employees. These networking channels which include WhatsApp and Facebook can enhance social interactions, support and acceptance at individual and organizational levels. Research limitations/implications: Social media has become a familiar tool for employees to use to discuss internal changes and policies within their organizations. Social media enhances the richness, reach, knowledge exchange and effective internal communication potential amongst organizational change stakeholders. Using social media, change recipients are now more empowered and connected with their leadership that ever before. It is now easier to facilitate decision making during the change formulation and implementation process. Practical implications: Social media applications have become necessary to ensure incremental and radical changes to the survival of dynamic businesses. The findings of this study are beneficial for change leaders and recipients of change to implement successful organizational change using social media tools. The effective and efficient use of social media applications helps organizations to foster knowledge amongst employees and they can address various critical issues, that is resistance to change, lower levels of knowledge sharing and support for change acceptance and lack of employee participation in decision making. Originality/value: There is an inadequate understanding regarding how SNAs play a role in facilitating the change process in both public and private sector organizations. This study offers a social mchange facilitation model with the help of social learning, social networking and social behaviourism theories.